QUALIDADE DA ÁGUA DE CORPOS HÍDRICOS LOCALIZADOS NO DISTRITO SANITÁRIO DO ITAQUI-BACANGA E AS IMPLICAÇÕES NA SAÚDE DA POPULAÇÃO DO ENTORNO. - CABRAL, Patricia Fernanda Pereira (2019)
Water represents one of the main environmental compartments. Its constant use in our daily activities and body composition translates how valuable this good is. However, what has been observed in recent years is the non-valorization of this resource through the gradual deforestation of riparian forests and the constant deposition of contaminants in the river and stream beds, which does not guarantee that this resource participates properly, hydrological cycle and changing compartments. This situation aggravates the access to quality water, and consequently, causes health problems, both by the consumption of contaminated water and food, as well as by diseases resulting from the lack of basic sanitation. In São Luís, this scenario is no different, because, although the Island is abundant in fresh and salty water, the population growth and the installation of industries in the region, which occurred in the last decades, hinders the dynamics of these ecosystems, since they are not respected the banks or effluent deposition in the riverbed. In this context, this research aimed to analyze the quality of water bodies located in the Itaqui-Bacanga Sanitary District in São Luís / MA, and the health implications of the residents of the region. Samples were collected in four distinct periods, taking place quarterly from May 2017 to February 2018. Physical-chemical analyzes were performed at the collection site using HORIBA Multi-Parameter Kit (Multi-Water Quality Checker U-50 Series), determining Electrical Conductivity, pH, Dissolved Oxygen and Temperature. The metals analysis took place at the Analytical Automation Research Laboratory, UFMA, using the Anodic Redissolution Voltammetry, determining Cd, Pb, Cu and Zn. Microbiological analyzes were analyzed at the Technological Pavilion, UFMA, using the Multiple Tube Technique to determine Escherichia coli. The questionnaires were applied by household and the research was approved by the UFMA Ethics Committee, with the opinion N ° 2290033.